Comprehensive assessment of рonderosa pine provenances in the north-east of Ukraine - Плотнікова, О. М.; Григорьєва, В. Г.; Лось , С. А.; Губін, Є. А. (Forestry and Forest Melioration, 2023)
Introduction The study of the geographic variability of tree species enables the selection of the most suitable provenances for a particular region and the development of forest seed zoning. In the native land in the USA, ponderosa pine (Pinus ponderosa Dougl. ex Laws.) has commercial value. This species is involved in research programs, in particular, related to the geographic variability study. In Ukraine, studies of the ponderosa pine provenances growth, development and condition have been going on for about 40 years. The aim of the study was to analyse the growth, condition and stem quality of ponderosa pine of different geographical origins and to determine the prospect provenances based on their comprehensive assessment in the conditions of north-eastern Ukraine. Materials and Methods The research was carried out in 40-year-old provenance trials of ponderosa pine in Kharkiv Forest Research Station, Ukraine. The forest site conditions were fresh rich sites. The growth characteristics, stem straightness, condition and presence of cones were assessed for each tree in all variants. The final conclusion regarding the value of provenances was made based on the results of their comprehensive assessment, which takes into account equally important indicators: growth intensity, condition, stem quality and reproductive development of the variants. Results The findings showed that at the age of 40, 40 out of 43 provenances of ponderosa pine were preserved. The viability of plants in the variants is made from 3 to 36%. The average diameter of the ponderosa pine variants ranged from 13.8 to 21.6 cm. Five variants significantly exceeded the control in diameter by 9.6–19.8 %. By this indicator, 9 variants were inferior to the control by 7.3–22.0 %. The average height of the variants was from 11.5 to 18.0 m; 13 variants significantly exceeded the control in height by 5.4–21.6 %, while 11 variants were inferior by 6.1–22.3 %. The part of straight-stemmed ponderosa pine trees of different origins ranged from 0 to 77.8 %. The condition index of the presented origins ranged from 1.0 to 2.8 points. At the time of the observation, there were cones from the previous and current years in most of the trees. No ponderosa pine undergrowth was found at the site, but the single self-sowing plants were available in open areas. According to the results of the comprehensive assessment, the sum of points 15.0–18.0 was scored by 13 provenances, which are promising for forestry with the aim of obtaining large-sized wood, in particular class A lumber. These are mainly of northern and eastern origins. Among them, the best variants were No 721 (Nebraska, 823 m a. s. l.), No 757 (South Dakota, 792 m a. s. l.), No 767 (New Mexico, 1,950 m a. s. l.), No 865 (Oregon, 1,310 m a. s. l.), No 866 (Washington, 488 m a. s. l.). For 24 provenances with a total score of 10.0–14.0, which were included in the relatively promising group, it is necessary to continue studying their growth and development in the future. Three provenances proved to be unpromising (the sum of points was 7.0–9.0), they may be excluded from further studies. Conclusions A high differentiation of ponderosa pine provenances was revealed in the intensity of growth by height and stem quality. Based on the results of the comprehensive assessment, 13 ponderosa pine varieties, mainly of northern and eastern origins, were identified as promising for forestry with the aim of obtaining large-sized wood, in particular class A lumber, in the conditions of north-eastern Ukraine. In the future, when creating stands with ponderosa pine, it is recommended to follow the planting scheme of 3.0 ? 3.0 m and provide timely thinning, as it will contribute to the resistance of the forest stand. 5 Figs., 2 Tables, 17 Refs.